LEVEL OF INVOLVEMENT OF LOCAL COMMUNITIES IN THE MANAGEMENT OF THE CONSERVATION AREA OF THE CHIPANJE CHETU PROGRAM IN NIASSA, MOZAMBIQUE - Azevedo, Sérgio Abílio; Nhamussua, Remígio Rangel; Cipriano, Erikson Leudério; Momade, Tuaifa Assane (Floresta, 2024)
Level of involvement of local communities in the management of the conservation area of the Chipanje Chetu program in Niassa, Mozambique. Developing projects for management of community conservation areas is a process that involves several entities, including governmental institutions, NGOs, private sectors and local communities. With the aim of evaluating the “level of involvement of local communities in the management of the conservation area of the Chipanje Chetu (our wealth) program in Niassa, Mozambique”, a participatory survey was carried out in the five communities. Semi-structured interviews, direct observation and document analysis were carried out, and subsequently analyzed using R Software, based on the analysis of pattern consistency, methodological triangulation and the citizen participation scale. It was observed that the participation of communities in the process of management and conservation of natural resources is at the delegated power level. The level of community participation and the degree of importance are associated with issues of benefit sharing and man-animal conflicts in this area.